Pertumbuhan Perkotaan Dalam Prespektif Sistem Ekologi - Nugroho, Iwan (Journal of Regional and City Planning, 2000)
Circumstances that accompany urban development could be explained by ecological system. Urban environment as a system could be separated into social and ecological system. Among them took place input and output flows as energy, material, and information creating a certain internal dynamic in each components and determining urban characteristics as whole. An outstanding mechanism in the ecologically urban system was homeostasis. Such mechanism was highly important to sustain the system against any conflicts beyond a demand and supply gap under a finite urban space. Such process was also to build social capital in which government, private sector, and people (three partiet) perform a high interrelationship to operate economic activities and to yield a high output and steady state. Recommended policies lead by homeostasis mechanism should be directed: (1) to improve urban economic productivity which is integrated into regional and rural development, (2) to increase productivity of urban poor people through improvement of social infrastructure and widening employment, (3) to avoid environment degradation as well as others consequences around poor people areas, and (4) to build an equal perception about urban development and related problems among stakeholders: government, private sectors, and people.